Effects of vibration techniques and expiratory flow acceleration on pain parameters in premature infants with pneumonia - Moura, Hévila Aragão; Cardoso, Rebekah Cintiah Carneiro; Torres, Daniel da Costa; Normando , Valéria Marques Ferreira; Rocha, Rodrigo Santiago Barbosa; Avila, Paulo Eduardo Santos (Pará Research Medical Journal, 2017)
Purpose: to evaluate the effects of vibration techniques and expiratory flow acceleration on pain parameters in preterm infants diagnosed with pneumonia hospitalized in the Neonatal Intensive Care Unit and Neonatal Intermediate Care Unit of the Santa Casa de Misericórdia Foundation of Pará, Brazil. Method: Randomized clinical trial, in which 28 preterm newborns were randomly divided into two groups: Group 1 - submitted to vibration technique and Group 2 - to expiratory flow acceleration. Both techniques were applied in a range of up to ten minutes, for three consecutive days. Pain indicators were assessed according to the Premature Infant Pain Profile (PIPP) at three times. For statistical analysis, the Friedman tests and Analysis of Variance were applied, the level of significance adopted was 5% (p <0.05). Results: Among the preterm infants in Group 1, 64.29% were male, with a mean gestational age of 33.50 ± 2.65 weeks; in Group 2, 57.14% were male, with mean gestational age 33.07 ± 2.84 weeks. Significant changes were observed in the heart rate index, between days, in Group 1 (p <0.05), and in facial mimetic aspects, between times (p <0.05) in both groups. Conclusion: The two techniques used did not cause changes that characterized the presence of pain in the newborns studied. However, it is suggested that new research is carried out in order to further elucidate the subject.